SOCIAL CAPITAL OF MINANG STUDENT ASSOCIATION RIAU UNIVERSITY - Pohan, Sawiyah; Indrawati, Indrawati; Marnelly, T Romi (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This research was conducted at the University of Riau, Bina Widya Campus, Jl. H.R Soebrantas, Pekanbaru, Riau. The purpose of the study was to determine the social capital that exists in the Minang University Student Association of Riau (IMAMI UNRI) and to find out what types of social capital exist in the Student Association. This study uses a descriptive qualitative method approach with research subjects eight informants, three key informants, and two triangulation. The results showed that the existing network within IMAMI UNRI was formed because of repeated interactions between them and the cooperation with outsiders was formed because of the bridge. The trust that exists between fellow Division Heads and outside parties in carrying out their duties begins with the existence of a network or relationship that has existed previously so that mutual trust arises. The norms that exist at IMAMI UNRI are the Articles of Association and Bylaws and the values that exist in Islam. These three elements must be present in IMAMI UNRI in order to survive as an organization. The type of social capital found is BondingSocial where work programs are carried out with the aim of bonding one another. Bridging Social which bridges the cooperative relationship with the Riau Minang Youth Association are alumni from IMAMI UNRI. Linking Social, there is a cooperative relationship between IMAMI UNRI and the Provincial Government of West Sumatra